Pengaruh Proporsi Labu Kuning (Cucurbita moschata Durch) Terhadap Mutu (Karbohidrat dan Serat) Serta Daya Terima Kue Kering (Cookies) - Nany Suryani; Firyal Yasmin; Dadan Jumadianor; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Yellow pumpkin is a local plant that is abundant in Indonesia. Yellow pumpkin is one of the foods that contain high fiber. Fiber in 100 grams the yellow pumpkin reaches 2.4 grams and carbohydrate content in 100 grams of yellow pumpkins reach 10 grams. Diversification is essential in order to increase the diversity of food in Indonesia. Diversification can be done using fresh yellow pumpkin is added to the making of cookies. This research was to know effect the proportion of yellow pumpkin (Cucurbita moschata Durch) on the quality (carbohydrate and crude fiber content) and the acceptance of cookies. (color, fragrance, texture and taste). The research design used was a completely randomized design. Test methods for carbohydrate content by the method of Luff-Schoorl and crude fiber by gravimetric method. Organoleptic testing methods with hedonic method (acceptance test). Statistical test for organoleptic using friedman test. Statistical test for carbohydrate content and crude fiber is One Way ANOVA. The results showed no effect the proportion of yellow pumpkin on carbohydrate content of cookies (p = 0,083). There is effect the proportion of yellow pumpkin on crude fiber content of cookies (p = 0,005). There is effect the proportion of yellow pumpkin on acceptance of cookies: color (p = 0,000), fragrance (p = 0,000), texture (p = 0,000) and taste (p = 0,000). Referring to the Indonesian National Standard (SNI) on quality requirements cookies, the best quality in terms of carbohydrate content was found on P5 treatment with an average value of 31,71% and the best quality in terms of crude fiber content is P5 treatment with average 3,86%.